Determination of heat transfer coefficients in direct contact latent heat storage systems. (25th December 2018) - Kunkel, Sven; Teumer, Tobias; Dörnhofer, Patrick; Schlachter, Kerstin; Weldeslasie, Yohana; Kühr, Martin; Rädle, Matthias; Repke, Jens-Uwe
Highlights: Heat transfer coefficients in a direct contact latent heat storage system were measured. Efficient optical temperature measurement in a rising oil phase. During melting of phase change material the heat transfer coefficient increases. The heat transfer phenomenon during melting of phase change material is changing. Abstract: This study presents a novel concept for a direct contact latent heat storage, which can be used for storing thermal energy from industrial waste heat or renewable energy systems. A storage medium, phase change material (PCM), and mineral oil heat transfer fluid (HTF) are placed in direct contact. The PCM and the oil are not miscible. The direct contact leads to an improved heat transfer and faster loading and unloading periods with a high storage density. Only affordable salt hydrates or mixtures of salt hydrates and additives are used as the PCM. For the scaling of the system, the heat transfer coefficient of the complex system must be known. A cylindrical channel inside the PCM is created, and the heat transfer coefficients between the oil and solid or melting PCM is investigated. Subsequently, the transmission in a real channel is described and discussed.